Development of a loop-mediated isothermal amplification targeting a gene within the pyruvate dehydrogenase complex, the pdhA gene, for rapid detection of Mycoplasma gallisepticum. (May 2015) - Zhang, Fanqing; Bao, Shijun; Yu, Shengqing; Cheng, Jinghua; Tan, Lei; Qiu, Xvsheng; Song, Cuiping; Dai, Yabin; Fei, Rongmei; Ding, Chan
Mycoplasma gallisepticum infections impose a significant economic burden on the poultry industry. In the current study, a loop-mediated isothermal amplification (LAMP) assay was developed and optimized to detect M. gallisepticum based on a gene within the pyruvate dehydrogenase complex, the pdhA gene, which codes for the major subunit (E1α) in the complex. The reaction conditions were optimized, and the specificity was confirmed by successful amplification of several M. gallisepticum strains, while no amplification was detected with 20 other major bacterial and viral pathogens of poultry. Additionally, the LAMP assay achieved 10-fold higher sensitivity than an existing polymerase chain reaction (PCR) method. The LAMP assay was applied to swab samples collected from poultry farms and compared with PCR. The positive detection rate was 20.2% (37/183) by LAMP and 13.1% (24/183) by PCR. The LAMP assay could provide a cost-effective, quick, and sensitive method for the detection of M. gallisepticum .